O caráter multifuncional de verbos volitivos do português do Brasil em gêneros jornalísticos - Baroni, Gabriela do Couto (2011)
Functionalism is a chain of contemporary linguistic studies that conceives language as a tool for social interaction. For functionalists, language must be studied from real communicative situations, oral or written, always been considered through the use by speakers. Based on this theory, this dissertation aims to analyze the usage of volitive verbs querer, mandar, deixar, desejar, pedir and exigir in two textual genres of the journalistic discursive domain: the opinion article and the interview, both from Veja magazine. Among the main principles of functionalism, we highlighted grammaticalization as the principle that guides this work. According to this principle, we find the proposal of Heine (1993) who defends that there are different stages that characterize the trajectory from full verb to Time marker, Aspect and Mode (Verb-to-TAM chain) on languages. These stages – totalizing seven – were called by the author Stage A, Stage B, and so on, until the Stage G. Each one of them have different characteristics that could show how the verb has been used by speakers. The full verbs are in the beginning of the continuum, that is to say, in Stages A and B. By the end, or in the Stages F and G, we find the affix or the inflection. The auxiliary presents characteristics of intermediate stages between the full verb and the inflection. Thus, within this proposal, we analyzed the usage of volitive verbs querer, mandar, deixar, desejar, pedir and exigir and we classified them according to the seven stages cited above. The analysis allows us to observe that the same verb may have different uses and, for this reason, be classified in different stages. It may also be observed that verbs from the same semantic group (volitive) are in different stages of the continuum and, by doing so, they present different characteristics among users.